Pengaruh Rasio Profitabilitas terhadap Financial Distress pada Perusahaan Sub Sektor Transportasi - Aini, Syaripah Qurrota (Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
This study aims to explain the effect of Profitability Ratios on Financial Distress in Transportation Sub-Sector Companies on the Indonesia Stock Exchange (IDX) for the 2019- 2021 period. The population used in this study is 35 transportation sub-sector companies listed on the Indonesia Stock Exchange in 2019-2021. The sampling technique used is purposive sampling in which the sample is taken based on certain criteria, so that only 105 companies are sampled from the 2019-2021 period. Hypothesis testing uses multiple linear regression analysis. The results of this study indicate that partially return on assets has a significant effect on financial distress, while partially return on sales and gross profit margin has no significant effect on financial distress in transportation sub-sector companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The results of the coefficient of determination show that return on assets, return on sales, and gross profit margin affect firm value by 22%, while 78% can be explained by other variables not used in this study.